The influence of age on Campylobacter jejuni infection in chicken - Han, Zifeng; Pielsticker, Colin; Gerzova, Lenka; Rychlik, Ivan; Rautenschlein, Silke (Developmental and comparative immunology, 2016)
Campylobacter jejuni (C. jejuni)-host-interaction may be affected by the maturation stage of the chicken's immune system and the developing gut microbiota composition. We compared these parameters between birds C. jejuni-inoculated at day one, 10, 22 and 31 post hatch. The highest C. jejuni-colonization rate and numbers of colony forming units (CFU) were detected in caecal content of day-one-inoculated birds while the lowest was detected in 22-days-old birds. The low bacterial colonization of 22-days-old chickens correlated with the most prominent immune reactions in this age group in comparison to other age groups. Age and C. jejuni-inoculation had a significant effect on lymphocyte numbers and cytokine expression levels in caecum as well as on gut flora composition. Overall, the immune response to C. jejuni is significantly influenced by the age of the infected chickens leading to differences in C. jejuni-colonization pattern between age goups.
Keywords: kampylobakterové infekce; nemoci ptáků; Aging; Bird Diseases; Immune response; Broiler; Cecum; Lymphocytes; Cells, Cultured; kur domácí; Campylobacter jejuni; Chickens; Campylobacter Infections; Gut microflora; interakce hostitele a patogenu; Age; cékum; střevní mikroflóra; lymfocyty; Animals; zvířata; stárnutí; Cytokines; Host-Pathogen Interactions; kultivované buňky; cytokiny; Gastrointestinal Microbiome